A Single Dose of an Avian H3N8 Influenza Virus Vaccine Is Highly Immunogenic and Efficacious against a Recently Emerged Seal Influenza Virus in Mice and Ferrets - Baz, Mariana; Paskel, Myeisha; Matsuoka, Yumiko; Zengel, James R.; Cheng, Xing; Treanor, John J.; Jin, Hong; Subbarao, Kanta (Journal of virology, 2015)
H3N8 influenza viruses are a commonly found subtype in wild birds, usually causing mild or no disease in infected birds. However, they have crossed the species barrier and have been associated with outbreaks in dogs, pigs, donkeys, and seals and therefore pose a threat to humans. A live attenuated, cold-adapted ( ca ) H3N8 vaccine virus was generated by reverse genetics using the wild-type (wt) hemagglutinin (HA) and neuraminidase (NA) genes from the A/blue-winged teal/Texas/Sg-00079/2007 (H3N8) (tl/TX/079/07) wt virus and the six internal protein gene segments from the ca influenza A virus vaccine donor strain, A/Ann Arbor/6/60 ca (H2N2), the backbone of the licensed seasonal live attenuated influenza vaccine. One dose of the tl/TX/079/07 ca vaccine induced a robust neutralizing antibody response against the homologous (tl/TX/079/07) and two heterologous influenza viruses, including the recently emerged A/harbor seal/New Hampshire/179629/2011 (H3N8) and A/northern pintail/Alaska/44228-129/2006 (H3N8) viruses, and conferred robust protection against the homologous and heterologous influenza viruses. We also analyzed human sera against the tl/TX/079/07 H3N8 avian influenza virus and observed low but detectable antibody reactivity in elderly subjects, suggesting that older H3N2 influenza viruses confer some cross-reactive antibody. The latter observation was confirmed in a ferret study. The safety, immunogenicity, and efficacy of the tl/TX/079/07 ca vaccine in mice and ferrets support further evaluation of this vaccine in humans for use in the event of transmission of an H3N8 avian influenza virus to humans. The human and ferret serology data suggest that a single dose of the vaccine may be sufficient in older subjects. IMPORTANCE Although natural infection of humans with an avian H3N8 influenza virus has not yet been reported, this influenza virus subtype has already crossed the species barrier and productively infected mammals. Pandemic preparedness is an important public health priority. Therefore, we generated a live attenuated avian H3N8 vaccine candidate and demonstrated that a single dose of the vaccine was highly immunogenic and protected mice and ferrets against homologous and heterologous H3N8 avian viruses.